At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's determine which of the given equations is equivalent to the original equation [tex]\(x^2 - 6x = 8\)[/tex].
First, we rewrite the given equation in a standard quadratic form:
[tex]\[ x^2 - 6x - 8 = 0 \][/tex]
Next, we consider the equivalence of this quadratic equation with each of the options provided.
### Option A: [tex]\((x - 6)^2 = 20\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 6)^2 = x^2 - 12x + 36 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 12x + 36 = 20 \][/tex]
Subtract 20 from both sides to bring it to a standard form:
[tex]\[ x^2 - 12x + 16 = 0 \][/tex]
This standard form does not match [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option A is not equivalent.
### Option B: [tex]\((x - 6)^2 = 44\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 6)^2 = x^2 - 12x + 36 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 12x + 36 = 44 \][/tex]
Subtract 44 from both sides to bring it to a standard form:
[tex]\[ x^2 - 12x - 8 = 0 \][/tex]
This standard form does not match [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option B is not equivalent.
### Option C: [tex]\((x - 3)^2 = 17\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 6x + 9 = 17 \][/tex]
Subtract 17 from both sides to bring it to a standard form:
[tex]\[ x^2 - 6x - 8 = 0 \][/tex]
This matches the original equation [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option C is equivalent.
### Option D: [tex]\((x - 3)^2 = 14\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 6x + 9 = 14 \][/tex]
Subtract 14 from both sides to bring it to a standard form:
[tex]\[ x^2 - 6x - 5 = 0 \][/tex]
This standard form does not match [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option D is not equivalent.
Thus, the equation equivalent to [tex]\(x^2 - 6x = 8\)[/tex] is:
[tex]\[ \boxed{(x - 3)^2 = 17} \][/tex]
So, the correct answer is option C.
First, we rewrite the given equation in a standard quadratic form:
[tex]\[ x^2 - 6x - 8 = 0 \][/tex]
Next, we consider the equivalence of this quadratic equation with each of the options provided.
### Option A: [tex]\((x - 6)^2 = 20\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 6)^2 = x^2 - 12x + 36 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 12x + 36 = 20 \][/tex]
Subtract 20 from both sides to bring it to a standard form:
[tex]\[ x^2 - 12x + 16 = 0 \][/tex]
This standard form does not match [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option A is not equivalent.
### Option B: [tex]\((x - 6)^2 = 44\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 6)^2 = x^2 - 12x + 36 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 12x + 36 = 44 \][/tex]
Subtract 44 from both sides to bring it to a standard form:
[tex]\[ x^2 - 12x - 8 = 0 \][/tex]
This standard form does not match [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option B is not equivalent.
### Option C: [tex]\((x - 3)^2 = 17\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 6x + 9 = 17 \][/tex]
Subtract 17 from both sides to bring it to a standard form:
[tex]\[ x^2 - 6x - 8 = 0 \][/tex]
This matches the original equation [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option C is equivalent.
### Option D: [tex]\((x - 3)^2 = 14\)[/tex]
Expand the left-hand side:
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
Substitute it back in the equation:
[tex]\[ x^2 - 6x + 9 = 14 \][/tex]
Subtract 14 from both sides to bring it to a standard form:
[tex]\[ x^2 - 6x - 5 = 0 \][/tex]
This standard form does not match [tex]\(x^2 - 6x - 8 = 0\)[/tex]. So, option D is not equivalent.
Thus, the equation equivalent to [tex]\(x^2 - 6x = 8\)[/tex] is:
[tex]\[ \boxed{(x - 3)^2 = 17} \][/tex]
So, the correct answer is option C.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.